Standar Akuntansi Keuangan Entitas Mikro, Kecil Dan Menengah Pada Jawara (Jaringan Wirausaha) Bojongsari - Erliana Erliana; Mahwiyah Mahwiyah (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
Good and correct financial records should be implemented by active MSMEs. The purpose of this activity is to provide partners with an understanding of the importance of transparent and accountable business financial management, provide knowledge regarding proper financial management in accordance with Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM) and assist MSMEs in preparing their business financial reports in accordance with SAK Generally accepted EMKM. This activity was carried out by the Bojongsari Depok Entrepreneurial Network (JAWARA). The activity method uses lecture and discussion techniques. The results obtained are that most of the administrators and owners of the MSME Entrepreneurial Network (JAWARA) are willing to keep records in an accountable manner. However, they hope that there will be in-depth and intense technical assistance, so that the preparation of the financial reports that will be carried out later is in accordance with the generally accepted SAK EMKM.